Concept of the bounded rationality in the conteхt of the postnonlassical paradigm - Давыдова, Ирина Анатольевна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article gives an analysis of the state of modern variation of the behavior theory – concept of the bounded ra-tionality. Preconditions of the rise of this conception are elucidated as alternative to classic and neoclassic paradigm. Connection of this conception with the postnonclassical methodology is observed. The author comes to the conclusion that combination of the theoretical models with experimental practice is perspective.